Integrating Information and Media Literacy into Pre-service Special Education Teachers Teaching and Learning - Bintoro, Totok; Winarsih, Murni (Jurnal Pendidikan dan Pengajaran, 2022)
The rise of the internet and the emergence of new digital devices require information users for information needs, access information effectively and efficiently, apply information, and use information effectively and efficiently. The purpose of this research is to develop a model for integrating information and media literacy into pre-service special education learning. The researcher applied the ADDIE approach. This research was conducted with a total of 214 students of the Special Special Education Pre-service Teacher Program, State University of Jakarta, Indonesia. The paper ends by proposing a theoretical model of The 5MIL (preparation, engagement, investigation, analysis, and sharing).Â